Profesionalitas Guru Pendidikan Agama Islam dalam Meningkatkan Kualitas Pembelajaran Siswa di Madrasah Tsanawiyah Bi’rul Ulum Sidoarjo - Bachtiar Hariadi; Moch Sodig; Nur Fazria M (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2022)
Teacher professionalism is a demand as an effort to improve the quality of learning. This study aims to capture the professionalism of Islamic Religious Education (PAI) teachers in improving the quality of student learning at Madrasah Bi'rul Ulum Sidoarjo. This research approach uses phenomenology. Collecting data using documentation, interviews, and observation. The professionalism of PAI teachers at Madrasah Bi'rul Ulum Sidoarjo appears in several aspects of competence, including competence in the learning process, psychological competence, noble character, wisdom, authority, socializing well, not only with students but also with parents and the community. around the madrasa. In addition, the supporting and inhibiting factors related to teacher professionalism are discussed in this study